2005
DOI: 10.3748/wjg.v11.i24.3655
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect and apoptosis induction of gambogic acid in human gastric cancer line BGC-823

Abstract: The inhibition of GA on human gastric cancer line BGC-823 was confirmed. This effect connects with the inducing apoptosis in BGC-823 cells and the molecular mechanism might be related to the reduction of expression of apoptosis-regulated gene bcl-2, and the improvement of the expression of apoptosis-regulated gene bax. The result was also confirmed in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 13 publications
1
83
0
Order By: Relevance
“…Apoptosis is one of the main cytotoxicity mechanisms of prenylated caged xanthones studied in several cancer cells. The growth inhibition of gambogic acid on human gastric carcinoma MGC-803 , BGC-823 (Liu et al, 2005), human malignant melanoma A375 cells , KKU-100 and KKU-M156 cells (Hahnvajanawong et al, 2010) was related to the apoptosis induction of which the molecular mechanism is the regulation of gene Bcl-2, an apoptosis inhibitor and Bax, an apoptosis inducer. Gambogic acid could downregulate the expression of Bcl-2 mRNA and upregulate the expression of Bax mRNA.…”
Section: Pharmaceutical Biologymentioning
confidence: 99%
“…Apoptosis is one of the main cytotoxicity mechanisms of prenylated caged xanthones studied in several cancer cells. The growth inhibition of gambogic acid on human gastric carcinoma MGC-803 , BGC-823 (Liu et al, 2005), human malignant melanoma A375 cells , KKU-100 and KKU-M156 cells (Hahnvajanawong et al, 2010) was related to the apoptosis induction of which the molecular mechanism is the regulation of gene Bcl-2, an apoptosis inhibitor and Bax, an apoptosis inducer. Gambogic acid could downregulate the expression of Bcl-2 mRNA and upregulate the expression of Bax mRNA.…”
Section: Pharmaceutical Biologymentioning
confidence: 99%
“…Animal Studies HepG2 cells (5 Â 10 6 ) were implanted subcutaneously in the right flank region of BALB/cA nude mice following protocols described in the literature (30). Briefly, when tumor size increased to 100 to 200 mm 3 , the mice were randomly divided into four groups consisting of equal numbers (six) of animals.…”
Section: Plasmids and Transfectionmentioning
confidence: 99%
“…In recent years, several studies have shown that gA can induce apoptosis and suppresses the proliferation of a variety of malignant cells, including hepatoma sMMc-7721 cells (9), gastric carcinoma Mgc-803 cells (10), Bgc-823 cells (11) and breast carcinoma McF-7 cells (12). gA mediates these responses by inhibiting tumor angiogenesis (13), acquiring chemotherapeutic resistance (14), and selectively binding tumor cells (9), among other mechanisms.…”
Section: Introductionmentioning
confidence: 99%